The role of atrial sensing for new‐onset atrial arrhythmias diagnosis and management in single‐chamber implantable cardioverter‐defibrillator recipients: Results from the THINGS registry. (25th February 2020) - Biffi, Mauro; Iori, Matteo; De Maria, Elia; Bolognesi, Maria Giulia; Placci, Angelo; Calvi, Valeria; Allocca, Giuseppe; Ammendola, Ernesto; Carinci, Valeria; Boggian, Giulio; Saporito, Davide; Grassini, Diego; et al.
Abstract: Introduction: Atrial tachycardia/fibrillation (AT/AF) episodes are common in implantable cardioverter‐defibrillator (ICD) recipients and can be undetected by standard single‐chamber devices. This study aims to explore whether a single‐lead ICD with an atrial dipole (ICD DX; BIOTRONIK SE & Co, Berlin, Germany) could improve the AT/AF diagnosis and management as compared to standard ICD (ICD VR). Methods and Results: We selected patients without AT/AF history from the THINGS registry which included consecutive patients implanted with ICD for standard indications. The ICD VR and the ICD DX groups included 236 (62.8%) and 140 (37.2%) patients, respectively, and had no significant differences in baseline characteristics. During a median follow‐up of 27 months, there were 7 AT/AF diagnoses in the ICD VR and 18 in the ICD DX group. The 2‐year incidence of AT/AF diagnosis was 3.6% (95% confidence interval [CI]: 1.6%‐9.6%) for the ICD VR and 11.4% (95% CI: 6.8%‐18.9%) for the ICD DX group (adjusted hazard ratio [HR]: 3.85 [95% CI: 1.58‐9.41]; P = .003). Initiation of oral anticoagulation (OAC) due to AT/AF diagnosis was reported in 15 patients. The 2‐year incidence of OAC onset was 3.6% (95% CI: 1.6%‐7.8%) for the ICD VR and 6.3% (95% CI: 3.0%‐12.7%) for ICD DX group (adjusted HR: 1.99 [95% CI: 0.72‐5.56]; P = .184). Conclusion: We observed that atrial sensing capability in single‐chamber ICD patients without evidence of atrial arrhythmias at implant is associated with a greater likelihood of detecting AT/AF episodes. The management of these diagnosed arrhythmias often led to clinical interventions, mainly represented by initiation of OAC therapy.